MULTILEVEL MODEL FOR THE DESCRIPTION OF SOLID-STATE PHASE TRANSITIONS IN MULTICOMPONENT ALLOYS - Trusov, P.V.; Volegov, P.S.; Isupova, I.L.; Kondratev, N.S.; Makarevich, E.S.; Nyashina, N.D.; Ostanina, T.V.; Sharifullina, E.R.; Shveikin, A.I.; Yants, A.Yu. (Perm Federal Research Centre Journal, 2016)
A three-level model of steel inelastic deformation with allowance for phase transformations under thermomechanical impact has been proposed. Three scale levels: macrolevel I (construction level), macrolevel II (level of representative macrovolume), mesolevel (crystallite level - separate grain or subgrain) have been included in the consideration. The levels are connected by means of internal variables that describe deformation and phase transformations at a deeper level. A computing algorithm in terms of the statistical approach for representative volume of meso- and macrolevel II on the basis of the formulated mathematical statement has been developed and realized. A parameter identification unit of the hardening law and adequacy check for computing results has been developed. Computing experiments for representative volume of macrolevel II under deformation by monoaxial stretching, a simple shift and complex loading have been conducted. The dependence of forming martensite on deformation intensity and deformation curves has been received for the specified loading types. The obtained calculated dependences are in good quantitative agreement with the known experimental data from the literature. The proposed model has been applied to describe the behaviour of a titanic alloy under high- temperature plastic deformation with dynamic recovery and recrystallization. Such processes of mechanical treatment as draft, constrained draft, simple shear have been considered. It is shown that the results of modelling, including the characteristics of the evolving structure, correspond to the experimental data.